2015
DOI: 10.18632/oncotarget.3924
|View full text |Cite
|
Sign up to set email alerts
|

miR-514a regulates the tumour suppressor NF1 and modulates BRAFi sensitivity in melanoma

Abstract: To identify 'melanoma-specific' microRNAs (miRNAs) we used an unbiased microRNA profiling approach to comprehensively study cutaneous melanoma in relation to other solid malignancies, which revealed 233 differentially expressed (≥ 2 fold, p < 0.05) miRNAs. Among the top 20 most significantly different miRNAs was hsa-miR-514a-3p. miR-514a is a member of a cluster of miRNAs (miR-506-514) involved in initiating melanocyte transformation and promotion of melanoma growth.We found miR-514a was expressed in 38/55 (69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 37 publications
7
78
0
9
Order By: Relevance
“…We observed that a group of miRNAs were consistently expressed either at a high level (e.g., let7a/b, miR-21 and miR-30d, Figure 6) or a low level (e.g., miR-34b, miR-26a, miR-137, miR-18b). These results are consistent with previous reports of deregulation of future science group Methodology Chatterjee, Stockwell, Rodger, Parry & Eccles these miRNAs in melanoma [43][44][45][46][47][48]. Furthermore, a group of miRNA showed distinct expression profiles between primary and melanoma patients.…”
Section: Mirna Profiling Of Primary and Metastatic Melanoma Tumorssupporting
confidence: 92%
“…We observed that a group of miRNAs were consistently expressed either at a high level (e.g., let7a/b, miR-21 and miR-30d, Figure 6) or a low level (e.g., miR-34b, miR-26a, miR-137, miR-18b). These results are consistent with previous reports of deregulation of future science group Methodology Chatterjee, Stockwell, Rodger, Parry & Eccles these miRNAs in melanoma [43][44][45][46][47][48]. Furthermore, a group of miRNA showed distinct expression profiles between primary and melanoma patients.…”
Section: Mirna Profiling Of Primary and Metastatic Melanoma Tumorssupporting
confidence: 92%
“…Our expression array data indicate that miR-7-5p functions to regulate large networks of genes in melanoma, and our network analysis supports the concept of regulation via “hub genes”, which includes RelA, a transcriptional regulator that itself regulates expression of many other genes, and hence altering miR-7-5p expression produces a significant “flow on” effect in terms of broadly altering gene expression [62]. We found that downregulation of RelA by miR-7-5p resulted in reduced expression of various canonical targets of NF-κB, including IL-1β, thus providing additional evidence for the indirect inhibition of broad transcriptional networks.…”
Section: Discussionsupporting
confidence: 67%
“…Further, we and others have shown that miR-7-5p is capable of sensitizing other resistant tumor types to targeted therapies, such as the EGFR tyrosine kinase inhibitor erlotinib [61]. In support of this concept, Stark et al have shown that miR-514a modulates BRAF inhibitor sensitivity in melanoma through its regulation of the tumor suppressor NF1 [62]. In addition, miR-7-5p could potentially augment the anti-melanoma immune response, by blocking expression of immunosuppressive cytokines, such as IL-6 [63].…”
Section: Discussionmentioning
confidence: 93%
“…miR-514a-3p (previously known as miR-514), located on chrXq27.3, has been demonstrated to be abnormally expressed in melanoma and metastatic RCC (25,26). In melanoma, Stark et al observed that miR-514a-3p negatively regulated nuclear factor 1 (NF1) and cyclin-dependent kinase 2 (CDK2) (26).…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, Stark et al observed that miR-514a-3p negatively regulated nuclear factor 1 (NF1) and cyclin-dependent kinase 2 (CDK2) (26). Wotschofsky et al assessed the expression of miR-514a-3p in 111 RCC patients (22 cases with metastases and 89 without) and the results revealed that miR-514a-3p was further downregulated in metastatic RCC compared with non-metastatic RCC tissues (25).…”
Section: Discussionmentioning
confidence: 99%